2005
DOI: 10.1145/1067860.1067864
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of sociability, usability, and community dynamics in an online health community

Abstract: The aim of this research is to develop an in-depth understanding of the dynamics of online group interaction and the relationship between the participation in an online community and an individual's off-line life. The 2½-year study of a thriving online health support community (Bob's ACL WWWBoard) used a broad fieldwork approach, guided by the ethnographic research techniques of observation, interviewing, and archival research in combination with analysis of the group's dynamics during a one-week period. Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
283
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(299 citation statements)
references
References 30 publications
14
283
0
2
Order By: Relevance
“…Research has found that such support can help patients adjust to the stress of living with and fighting against their diseases [5,6,7] and is a consistent indicator of survival [8]. An OHC also serves as an outlet for users' emotional needs and improve their offline life [9]. Thus active engagement in an OHC has been found to be therapeutic to users [10] and it is important to keep users engaged in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that such support can help patients adjust to the stress of living with and fighting against their diseases [5,6,7] and is a consistent indicator of survival [8]. An OHC also serves as an outlet for users' emotional needs and improve their offline life [9]. Thus active engagement in an OHC has been found to be therapeutic to users [10] and it is important to keep users engaged in the community.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of design implications, the simulation results call for reconsideration of well-established beliefs in the effectiveness of a narrow focus (Maloney-Krichmar & Preece, 2005 ) and community-level moderation (Preece, 2000 ). While these practices remain useful for some communities, our research suggests a contingency view of online community design.…”
Section: Following the Roadmap: Using Abm To Inform The Design Of Onlmentioning
confidence: 99%
“…For example, communities with a tradition of aggressive responses or put-downs, if they manage to exist at all, will be more like arenas in which there is a relatively small number of participants with many onlookers [4]. Other communities may evolve over time to develop strong norms of acceptable behaviour [3,5]. Both are examples of social adaptations, that is, sociability.…”
Section: Background: Developing Online Communitiesmentioning
confidence: 99%
“…For example, in one online community studied, interviews with participants revealed that they were happy with an older product and saw no need for upgrading to state-of-the-art software. The major concern for these participants was 24/7 availability of the server and consequent access to their community [3,5].…”
Section: Using Established Techniques For Evaluating Online Communitiesmentioning
confidence: 99%
See 1 more Smart Citation